Ambientes de confluência no contexto da rede de drenagem: exemplo da bacia hidrográfica do rio Ivaí - estado do Paraná - Santos, Vanessa Cristina dos [UNESP] (2015)
River channel confluences are sites with continuous changes in the flow structure and the sediment transport. Confluences are also places in the river network operating complex interactions between material and energy, provided by the combination of different patterns flows. This particular dynamic can influence since ecological aspects to spatial planning considerations and occupation of space. The main objective of this research is to analyse the confluence environments considering the geomorphological and hydro-sedimentary aspects and evaluate the influence of local and regional factors on these aspects. This research assumes that the morphology of confluences is conditioned by aspects of river network as geomorphometric (basin size, circularity, drainage density, confluence angle and others), hydrosedimentological (liquid and solid discharge regime and load transported) and geological. To achieve this objective, first it evaluated the quality of geomorphometric data extracted from different Digital Elevation Models considering the different acquisition methods (sensors) and the scale (resolution), to then evaluate geomorphometric aspects of river networks. It also conducted regionalization and estimation average flow and production of suspended load, both the main channel of the studied watershed, and for its tributaries. Also it was evaluated some confluences in the field work to obtain data concerning about flow structure, morphology and granulometric composition essential for understanding the local dynamics of the confluences. Finally, all the results were analysed using data mining techniques for assessing the influence of regional and local aspects in the configuration of confluences. For this study, it took as example the Ivaí watershed, as this has a dam free condition on your main channel and the heterogeneity of its physiographics properties that influence the variability in geomorphological and hydro-sedimentary aspects...